2019
DOI: 10.30699/ijmm.13.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibiotic Resistance Pattern of Meropenem and Piperacillin- Tazobactam in Multi Drug Resistant Acinetobacter baumannii Isolates by Flow Cytometry Method

Abstract: Article Subject: Antibiotic Resistance 10.30699/ijmm.13.3.194 Background and Aims: Flow cytometry is a rapid method that can analyze thousands of cells per second and can be used for determination of microbial populations and determination of bacterial antimicrobial susceptibility. In this study antibiotic resistance pattern of Acinetobacter baumannii isolates by flow cytometer was evaluated. Materials and Methods: 55 isolates of A. baumannii were isolated from clinical specimen of patients and were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Despite most reports and in agreement with the results of studies by Rahimi and Rezaie Keikhaie et al, Acinetobacter spp. isolates showed partly good sensitivity to gentamicin (40%) (37,38). In contrast to the results of the current study, Mortazavi et al (39) reported very high resistance to gentamicin and amikacin simultaneously among 80 A. baumannii strains from Ahvaz, south-west Iran.…”
Section: Discussioncontrasting
confidence: 95%
“…Despite most reports and in agreement with the results of studies by Rahimi and Rezaie Keikhaie et al, Acinetobacter spp. isolates showed partly good sensitivity to gentamicin (40%) (37,38). In contrast to the results of the current study, Mortazavi et al (39) reported very high resistance to gentamicin and amikacin simultaneously among 80 A. baumannii strains from Ahvaz, south-west Iran.…”
Section: Discussioncontrasting
confidence: 95%